1970
DOI: 10.3329/bjms.v8i3.3985
|View full text |Cite
|
Sign up to set email alerts
|

Width of attached gingiva in an Indian population: A descriptive study

Abstract: Objectives: Attached gingiva is important for maintaining periodontium in a healthy state. The present study tries to find the normal values of width of attached gingiva in a periodontally healthy Indian population. Material and Methods: The width of attached gingiva was measured with a periodontal probe in periodontally healthy patients attending the periodontics department. Descriptive statistical analysis was done to get the mean, which will represent the normal values of width of attached gingiva for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…Kolte et al included 3 different age groups (16-24 years, 25-39 years, and > 40 years; n = 20 males, 20 females in each group) and reported smaller mean amounts of attached gingiva in the maxilla compared to the present study. Adesola et al [25] also investigated the influence of gender on the WAG of 54 females and 19 males in a Nigerian population and found no significant [15] reported a higher WAG in Indian females than in males. It should be noted that the authors analyzed the measurements on the maxillary and mandibular central incisors, the premolars, and molars, but they did not present gender-related positional details.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kolte et al included 3 different age groups (16-24 years, 25-39 years, and > 40 years; n = 20 males, 20 females in each group) and reported smaller mean amounts of attached gingiva in the maxilla compared to the present study. Adesola et al [25] also investigated the influence of gender on the WAG of 54 females and 19 males in a Nigerian population and found no significant [15] reported a higher WAG in Indian females than in males. It should be noted that the authors analyzed the measurements on the maxillary and mandibular central incisors, the premolars, and molars, but they did not present gender-related positional details.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the influence of age on the WAG and CCL, gender may also have an effect; although, reports are contradictory [6,14]. In an Indian population, the gingiva was wider in females than males [15], while other studies have found no correlation with gender [14].…”
Section: Introductionmentioning
confidence: 95%
“…In a study by Shaju Jacob et al [15], variations in the WAG were identi ed across various regions of oral cavity, with the widest measurements in the upper central incisors and the narrowest in the lower molars.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, similar variations in the WAG were observed in both arches. Variations in WAG in various studies might be due to different methods used to locate mucogingival junctions (functional versus staining) or possible true ethnical differences [10,15,16,31].…”
Section: Resultsmentioning
confidence: 99%
“…2,3 The average width of the attached gingiva in the maxillary anterior region is established to be 3.5-4.5 mm. 4 Furthermore, Miller stated that the frenum is considered aberrant when it is unusually wide or there is no apparent zone of attached gingiva along the midline or the interdental papilla shifts when the frenum is extended. 5 The aberrant frenum appears inordinately large and/or attached close to the gingival margin and the residual fibers persist between maxillary central incisors attaching to the periosteum and connective tissue of the interincisal suture.…”
Section: Introductionmentioning
confidence: 99%